Dendrite‐accelerated thermal runaway mechanisms of lithium metal pouch batteries - Xu, Xiang‐Qun; Cheng, Xin‐Bing; Jiang, Feng‐Ni; Yang, Shi‐Jie; Ren, Dongsheng; Shi, Peng; Hsu, HungJen; Yuan, Hong; Huang, Jia‐Qi; Ouyang, Minggao; Zhang, Qiang (SusMat (Online), 2022)
High‐energy‐density lithium metal batteries (LMBs) are widely accepted as promising next‐generation energy storage systems. However, the safety features of practical LMBs are rarely explored quantitatively. Herein, the thermal runaway behaviors of a 3.26 Ah (343 Wh kg−1) Li | LiNi0.5Co0.2Mn0.3O2 pouch cell in the whole life cycle are quantitatively investigated by extended volume‐accelerating rate calorimetry and differential scanning calorimetry. By thermal failure analyses on pristine cell with fresh Li metal, activated cell with once plated dendrites, and 20‐cycled cell with large quantities of dendrites and dead Li, dendrite‐accelerated thermal runaway mechanisms including reaction sequence and heat release contribution are reached. Suppressing dendrite growth and reducing the reactivity between Li metal anode and electrolyte at high temperature are effective strategies to enhance the safety performance of LMBs. These findings can largely enhance the understanding on the thermal runaway behaviors of Li metal pouch cells in practical working conditions. The thermal runaway features of Li | NCM523 pouch cells (343 Wh kg−1) over the whole life cycle are analyzed quantitatively. The formation of large amounts of dendritic Li and SEI is observed as cycling depth increasing, leading to strong exothermic reactions between SEI components and LiPF6, dendritic Li and electrolytes.